Association between Gross National Income per capita and COVID-19 vaccination coverage: a global ecological study - Dennis Ogeto Nyachoti; Pierre Fwelo; Andrew E. Springer; Steven H. Kelder (BMC, 2023)
Abstract Background Coronavirus 2019 (COVID-19) pandemic has claimed over six million lives and infected more than 650 million people globally. Public health agencies have deployed several strategies, including rolling out vaccination campaigns to curb the pandemic, yet a significant proportion of the global population has not received the COVID-19 vaccine. We assessed differences in COVID-19 vaccination coverage by Gross National Income (GNI) per capita of WHO members (i.e., countries, areas, and territories, n = 192) and by WHO member regions (n = 6). Methods Using an ecological study design, we analyzed publicly available data from the WHO website merged with the World Bank's GNI per capita data. We included a total of 192 WHO members and six WHO regions in the analysis. We utilized negative binomial regression to assess the associations between the GNI per capita and COVID-19 vaccination coverage (cumulative number of persons fully vaccinated and/or received at least one dose of the vaccine per 100 population), and ANOVA test to assess the differences in vaccination coverage per WHO regions. Results Low GNI per capita WHO members had significantly lower full vaccination coverage (aRR 0.30, 95% CI 0.22-0.40) compared to high GNI per capita WHO members. These members were also 66% less likely to receive at least one dose of the vaccine (aRR 0.34, 0.26-0.44) relative to high GNI per capita WHO members. Africa region had a significantly lower fully vaccination coverage (aRR 0.71, 95% CI 0.36-0.54) and received at least one dose of the COVID-19 vaccine (aRR 0.78, 95% CI 0.62-0.99) than Europe region. Conversely, the Western Pacific region had significantly higher fully vaccination coverage (aRR 1.40 95% CI 1.12-1.74) and received at least one dose of COVID-19 vaccines (aRR 1.40 95% CI 1.14-1.73) relative to European region. Conclusion WHO members with low GNI per capita and the African region reported significantly lower COVID-19 vaccination coverage than those with high GNI per capita or other regions. Efforts to strengthen and promote COVID-19 vaccination in low-income WHO countries and African region should be scaled up.